The performance of photovoltaic (PV) systems : modelling, measurement and assessment - Pearsall, Nicola; Ohio Library and Information Network (Cambridge : Woodhead Publishing, 2017)
The Performance of Photovoltaic (PV) Systems: Modelling, Measurement and Assessment explores the system lifetime of a PV system and the energy output of the system over that lifetime. The book concentrates on the prediction, measurement, and assessment of the performance of PV systems, allowing the reader to obtain a thorough understanding of the performance issues and progress that has been made in optimizing system performance.
Includes bibliographical references and index.
Keywords: Photovoltaic power systems; Photovoltaic power generation; Solar cells; Photovoltaic power systems; Photovoltaic power generation; Solar cells